Left brachiocephalic vein aneurysm: a case report - Harushi Ueno; Mari Yazawa; Hideki Tsubouchi; Keita Nakanishi; Tomoshi Sugiyama; Yuka Kadomatsu; Masaki Goto; Naoki Ozeki; Shota Nakamura; Takayuki Fukui; Masato Mutsuga; Toyofumi Fengshi Chen Yoshikawa (Surgical Case Reports)
Abstract Background Aneurysm of the left brachiocephalic vein is a very rare clinical disease and only 40 cases have been reported so far. Case presentation The patient was a 61-year-old woman with no related medical history. She underwent CT to investigate the cause of a cough and a mass was noted in the anterior mediastinum. Dynamic computed tomography with contrast medium injected into the left basilic vein demonstrated the venous aneurysm with blood flow to the left brachiocephalic vein. The patient had no symptoms, but because of the risk of pulmonary infarction and aneurysm rupture, the aneurysm was surgically resected. A median sternotomy was a reasonable approach because of the fragility of the venous aneurysm wall with little working space in the anterior mediastinum. Conclusions We diagnosed an aneurysm of the left brachiocephalic vein on preoperative imaging and excised it through a median sternotomy. The venous wall was thin and fragile in some areas and so this approach was appropriate in view of the possibility of intraoperative injury.